Pharaprase in Article the Impact of Covid-19 in Education - Yuli Indah Pratiwi; Fathia Asmadiah Lenggana; Hijjah Riani; Fahri Irawan Wijaya; Emeliya Sukma Dara D (e-Journal of Linguistics, 2023)
This study aims to analyze and provide examples of paraphrasing asentence contained in an article, this article is entitled about theinfluence of COVID-19 in the world of education and the economy inIndonesia. The article that we take as an example is an articlewritten by our friend. Paraphrases can not only be used in speeches,dialogues, songs of daily life and other literary works, butparaphrases can also be used in a scientific work, for example, inarticles, mini-research thesis and others. Therefore, the researcher isvery interested in paraphrasing this scientific work, namely thearticle. This researcher uses a qualitative method, by collecting data,then the researcher paraphrases the sentences that can beparaphrased according to the researcher. then the data is taken andcollected, then analyzed with the theory contained in the paraphrase,so it really supports this research. Paraphrasing is the restating of asentence such that both sentences would generally be recognized aslexically and syntactically different while remaining semanticallyequal.